5+8k=43

Simple and best practice solution for 5+8k=43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+8k=43 equation:


Simplifying
5 + 8k = 43

Solving
5 + 8k = 43

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 8k = 43 + -5

Combine like terms: 5 + -5 = 0
0 + 8k = 43 + -5
8k = 43 + -5

Combine like terms: 43 + -5 = 38
8k = 38

Divide each side by '8'.
k = 4.75

Simplifying
k = 4.75

See similar equations:

| 5x+2x=2(x+5) | | (x-5)*(x-8)=40 | | (4x^2)(.02+x^2)= | | 0.7x+0.2=0.9x-0.8 | | 18=2b+5-1 | | X+(x-5)+(2x)=59 | | 3-7+12w=10w+30+2 | | x(4x+10)=0 | | 3-7+5+13-2= | | 3a+4b-5c= | | 5y-3=12y+60 | | 14x+16=3(x-1) | | 72c-108=7c-3 | | 6x=24x+36 | | 6x-3=1.222 | | -2,992+272m=0 | | 20+2x=2.50x | | f=5+0.20d | | .778(6x-3)=2 | | 2726=29(p+35) | | 3ot-20=70 | | 16-7t=6-5t | | 3x+4-6x+2= | | -3(x-6)=-3 | | -2x^2-6x+3=0 | | 4x-3*-17=26 | | -8(2t+7)=-136 | | 25=x+x(.323) | | (4x-7)=2 | | 2(f-5)=-16 | | 52=2v+16 | | 180x+75y=165 |

Equations solver categories